Dados biométricos em esquistossomóticos adultos, Bahia (Brasil) Biometric data in adult schistosomotics of Catolândia, Bahia, Brazil - José Tavares-Neto; Eduardo Forleo-Neto; Ernesto Wilhelms-Neto; Aluízio Prata (Universidade de São Paulo, 1988)
De dezessete indivíduos esquistossomóticos, hepatosplênicos, pareados com outros dezessete controles, hepatointestinais, da mesma região, foram aferidas 17 medidas antropométricas. Todas as pessoas tinham de 21 a 50 anos de idade. Esta e outros critérios foram previamente estabelecidos como fatores de pareamente, de inclusão e exclusão no estudo. Porém, não se observou diferenças estatísticas entre as médias dos dois grupos de pacientes. Seventeen antropometric measurements were evaluated from seventeen hepatosplenic schistossomotic individuals paired with seventeen control hepato-intestinal schistosomotic patients. All of them were from the same region, and all of them belonged to an age group ranging from 21 to 50 years. Age and other criteria were previously established, such as pairing factors, to determine inclusion in or exclusion, from the study. However, statistical differences were not observed between the averages of the two groups of patients.